Yiqihuoxue decoction (GSC) inhibits mitochondrial fission through the AMPK pathway to ameliorate EPCs senescence and optimize vascular aging transplantation regimens - Yinan Liu; Zenghui Niu; Xue Wang; Chengkui Xiu; Yanhong Hu; Jiali Wang; Yan Lei; Jing Yang (BMC, 2024)
Abstract Background During the aging process, the number and functional activity of endothelial progenitor cells (EPCs) are impaired, leading to the unsatisfactory efficacy of transplantation. Previous studies demonstrated that Yiqihuoxue decoction (Ginseng-Sanqi-Chuanxiong, GSC) exerts anti-vascular aging effects. The purpose of this study is to evaluated the effects of GSC on D-galactose (D-gal)induced senescence and the underlying mechanisms. Methods The levels of cellular senescence-related markers P16, P21, P53, AMPK and p-AMPK were detected by Western blot analysis (WB). SA-β-gal staining was used to evaluate cell senescence. EPCs function was measured by CCK-8, Transwell cell migration and cell adhesion assay. The morphological changes of mitochondria were detected by confocal microscopy. The protein and mRNA expression of mitochondrial fusion fission Drp1, Mff, Fis1, Mfn1, Mfn2 and Opa1 in mitochondria were detect using WB and RT-qPCR. Mitochondrial membrane potential, mtROS and ATP of EPCs were measured using IF. H&E staining was used to observe the pathological changes and IMT of the aorta. The expressions of AGEs, MMP-2 and VEGF in aorta were measured using Immunohistochemical (IHC). The levels of SOD, MDA, NO and ET-1 in serum were detected by SOD, MDA and NO kits. Results In vitro, GSC ameliorated the senescence of EPCs induced by D-gal and reduced the expression of P16, P21 and P53. The mitochondrial morphology of EPCs was restored, the expression of mitochondrial Drp1, Mff and Fis1 protein was decreased, the levels of mtROS and ATP were decreased, and mitochondrial function was improved. Meanwhile, the expression of AMPK and p-AMPK increased. The improvement effects of GSC on aging and mitochondrial morphology and function were were hindered after adding AMPK inhibitor. In vivo, GSC improved EPCs efficiency, ameliorated aortic structural disorder and decreased IMT in aging mice. The serum SOD level increased and MDA level decreased, indicating the improvement of antioxidant capacity. Increased NO content and ET-1 content suggested improvement of vascular endothelial function. The changes observed in SOD and MMP-2 suggested a reduction in vascular stiffness and the degree of vascular damage. The decreased expression of P21 and P53 indicates the delay of vascular senescence.